Digital learning transformation in strengthening self-resilience - Armawi, Armaidy; Makmur, Chesa Syaqira; Septiyanti, Murni; Wahidin, Darto (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
The Covid-19 pandemic has forced teachers to conduct learning activities online through digital technology. As they are accustomed to the conventional or offline learning process, this digital-based learning transformation has resulted in teachers experiencing shock culture and students affected immensely. The current research aims to describe the strategies applied for digital-based learning, examine challenges in digital-based learning, and identify digital-based learning impacts on students' self-resilience. It employs the qualitative research method, and the data consist of primary and secondary data. The primary one is derived from the observation of focus group discussion and documentation. The secondary one is in the form of references from books, journals, and articles. By data reduction and conclusion drawing in a descriptive qualitative analysis, the findings show that using learning application varies depending on the teachers' capability and convenience, and agreement from the institution. The only learning media used in the format are videos and pictures, considering the weak internet bandwidth and limited internet quota. The challenges in digital-based learning should be the point of attention for both teachers and parents. The impacts resulted from this digital-based learning system on students' self-resilience are considerable. Supports from family and school must be wholly given to reinforce students' self-resilience.